Social Support Networks in Quebec's English-speaking Communities : Building Community Vitality Through Social Capital Strategies - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
This report arises in response to one of the objectives of the “We Can Act” project sponsored by the Community Health and Social Services Network (CHSSN). The CHSSN is a network of 60 community resources, associations, foundations, public institutions and other stakeholders dedicated to the development of partnerships in health and social services for English‐speaking communities in Quebec. The CHSSN promotes knowledge‐based community development as a means for communities to enhance their vitality and improve the health and well‐being of their members. Consistent with the population health approach, CHSSN sponsors projects and partnerships which address health determinants affecting the health status of communities as well as supportive strategies to attain a sustainable health and social service system.
Keywords: Official Language Minority Community (OLMC)